Content-based organisation, analysis and retrieval of soccer video. (19th July 2010) - Yu, Junqing; He, Yunfeng; Sun, Kai; Ouyang, Xingming
A hierarchical organising model based-on MPEG-7 is introduced to effectively represent high-level and low-level information in soccer video. To effectively retrieve highlight clip of soccer video, adaptive abstraction is designed based on the excitement time curve, and an XML-based query scheme for semantic search and retrieval is proposed based on the hierarchical model. For retrieval, XQuery, a XML query language, is employed in the proposed querying framework. The proposed framework employs visual, audio, and cinematic features, and can be scalable to different preferences and requirements. Its efficiency, effectiveness, and the robustness of the proposed framework have been demonstrated over our extensive experiments.